Development of E-Module Ethnobotany Based on Lombok Local Wisdom to Improve Student Motivation and Learning Outcomes in High School - M Rofi'i; Retno Sri Iswari; Dyah Rini Indriyanti (Universitas Negeri Semarang, 2022)
This study aims to determine the characteristics of the E-module, the validity of the Lombok local wisdom E-module, the readability of students' responses to the E-module, the effectiveness of the E-module in increasing motivation and learning outcomes, and the practicality of the developed E-module. This type of research is the development of research and development (R&D) to see the level of validity of the Lombok local wisdom E-module E-module which was developed by a research procedure by applying 9 steps, preliminary studies, product drafting, design validation, design revisions, limited scale trials, revision of the results of limited trials, large-scale trials, product revisions, practicality and readability tests and finally the final product, this product is an E-module of Lombok's local wisdom ethnobotany. The results of this study indicate that the Lombok local wisdom E-module ethnobotany obtained 76.00% declared valid by expert lecturers with an average value, material expert validation obtained an average value of 76.00% while media expert validation was 92.18%. The results of a large-scale trial of 75 students from each school obtained an average student response of 87.17%, 84.25% and 81.83%. The results of the N-gain value from each school showed that there was an increase in student learning outcomes after using the E-module in the learning process, namely 0.86, at SMA NW Anjani in the high category 0.78, at MA Muallimin NW Anjani school in the high category. the last high of 0.78. at SMA NW Suralaga classified as high category. Furthermore, the results of the practicality test questionnaire filled out by 3 biology teachers obtained average results of 95.00, 98.50 and 97.50 from each school. And this research produces an effective and practical E-module for class X IPA SMA. These results indicate that the product developed is an E-module of Lombok local wisdom ethnobotany as a supplement to plant material to increase motivation and learning outcomes in high school.